Multiple regression analysis of technical characteristic parameters and athletic performance of elite male long jumpers - Zhang, J.; Xing, R. (3rd Asia Sport Science Conference (ASSC), June 24-25, 2022, 2022)
China's long jump athletes had broken Asian records many times. But in recent years, their performance has been stagnant, and even has a certain downward trend. There is already a gap between the overall level and the peak level of the world. Therefore, it is an urgent problem to be solved in the field of long jump by refining the training objectives, finding the sensitive parameters that affect the long jump performance, and then improving the special performance. The improvement of the long jump athlete's performance will be affected by improving the movement technique and their physical fitness (Liu, 2000). At present, researches in the field of long jump mostly focus on comparing Chinese athletes and world high-level athletes, as well as the correlation between the characteristics of speed parameters and performance, but there is little research on the comprehensive effects of multiple technical movement parameters on performance. The performance of the long jump is also the result of the joint influence of many factors. Therefore, it is particularly important to conduct an overall and comprehensive analysis of the technical action parameters of the long jump.